IMPACT OF COUNSELLING ON KNOWLEDGE AND ATTITUDE TOWARDS COMMUNITY-ACQUIRED PNEUMONIA IN THE GERIATRIC PATIENTS - Baranidharan S; Majid Hussain A; Jeeva S; Senthil M (The Bioscan, 2025)
Backgrounds: Community-acquired pneumonia is a significant health problem in geriatric people because of atypical symptom presentation and less awareness of preventive strategies. Limited knowledge and poor attitudes in elderly people contributes to delayed diagnosis. The aim of the research is to evaluate the counselling effect on the knowledge and attitude of older individuals towards community acquired pneumonia that focuses on awareness of disease, risk perception and preventive practice. Methods: A descriptive cross-sectional interventional study was led among 480 geriatric patients (>60 years). A pre-structured multiple-choice questionnaire was used to assess the baseline knowledge and attitude followed by 30-60 minutes counselling session. Post-intervention evaluation was done through same questionnaire. Result: The study showed significant improvement in patient awareness cross all factors. Correct spotting of community acquired pneumonia were increased from 45.8% to 66.6%, bacterial etiology knowledge rose from 33.3% to 72.9% and risk factor recognition such as smoking increased from 26.2% to 80.4%. Moreover, vaccine awareness progressed from 55% to 94.5%. Conclusion: The targeted counselling significantly increased the knowledge and adopts positive health attitude in older population regarding community acquired pneumonia. These findings assist integration of educational counselling into routine geriatric care to enhance early detection and preventive measures.